2021
DOI: 10.12688/f1000research.52894.1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of information in news media reports about the effects of health interventions: Systematic review and meta-analyses

Abstract: Background Many studies have assessed the quality of news reports about the effects of health interventions, but there has been no systematic review of such studies or meta-analysis of their results. We aimed to fill this gap (PROSPERO ID: CRD42018095032). Methods We included studies that used at least one explicit, prespecified and generic criterion to assess the quality of news reports in print, broadcast, or online news media, and specified the sampling frame, and the selection criteria and technique. We as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 83 publications
0
14
0
1
Order By: Relevance
“…MB and GC separately analysed the quality of online information based on whether it met the following 10 criteria. The selection of said criteria was based on the only available SR of the quality of information on health interventions 59 and two other relevant papers. 60 61 The criteria used were: (1) provides references or links to scientific publications; (2) explains the conclusions of scientific publications; (3) quantifies relative effects; (4) quantifies absolute effects; (5) acknowledges some research limitations (eg, preliminary results, small studies, conflicts of interests and differing results between studies); (6) generally discusses certainty of evidence (eg, aligning wording depending on whether the studies are observational or experimental) 62 ; (7) reports potential harms; (8) reports on available alternatives; (9) discusses intervention costs; and (10) does not make arguments based on personal experiences or anecdotes.…”
Section: Quality Of Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…MB and GC separately analysed the quality of online information based on whether it met the following 10 criteria. The selection of said criteria was based on the only available SR of the quality of information on health interventions 59 and two other relevant papers. 60 61 The criteria used were: (1) provides references or links to scientific publications; (2) explains the conclusions of scientific publications; (3) quantifies relative effects; (4) quantifies absolute effects; (5) acknowledges some research limitations (eg, preliminary results, small studies, conflicts of interests and differing results between studies); (6) generally discusses certainty of evidence (eg, aligning wording depending on whether the studies are observational or experimental) 62 ; (7) reports potential harms; (8) reports on available alternatives; (9) discusses intervention costs; and (10) does not make arguments based on personal experiences or anecdotes.…”
Section: Quality Of Informationmentioning
confidence: 99%
“…The first SR of the quality of information on health interventions in traditional media outlets and online resources also found room for improvement as regards health news. 59 However, nutrition-related information is especially prone to poor quality and may contribute to public misconceptions about dietary strategies targeting the gut microbiome and health. [80][81][82][83][84] In our study, retail sites intended for direct purchase and advertisements were excluded from the analysis; nevertheless, a quarter of the analysed web pages were commercial.…”
Section: Open Accessmentioning
confidence: 99%
“… 1 Despite many initiatives in this area, 2 3 journalists generally receive no routine training in how to interpret or present medical research, 4 5 and studies have found the quality of media coverage of medicine is often poor globally. 6 Research has shown that media stories frequently emphasise the potential benefits of health interventions and under-report the harms, ignore important conflicts of interest, report numbers in misleading ways and frequently fail to report important study limitations. 6 7 As the media has a powerful influence on the public’s perceptions, behaviours and utilisation of healthcare, 8 9 quality medical reporting is essential to ensure accurate portrayal of health and science information, which in turn can shape the health of the population.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Research has shown that media stories frequently emphasise the potential benefits of health interventions and under-report the harms, ignore important conflicts of interest, report numbers in misleading ways and frequently fail to report important study limitations. 6 7 As the media has a powerful influence on the public’s perceptions, behaviours and utilisation of healthcare, 8 9 quality medical reporting is essential to ensure accurate portrayal of health and science information, which in turn can shape the health of the population. 10 Given evidence has grown on the broader problems of medical excess, including overdiagnosis and overuse, 11–13 the need for quality media reporting has become a greater priority.…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite many initiatives in this area, 2 3 journalists generally receive no routine training in how to interpret or present medical research, 4 5 and studies have found the quality of media coverage of medicine is often poor globally. 6 Research has shown that media stories frequently emphasise the potential benefits of health interventions and under-report the harms, ignore important conflicts of interest, report numbers in misleading ways and frequently fail to report important study limitations. 6 7 As the media has a powerful influence on the public's perceptions, behaviours and utilisation of healthcare, 8 9 quality medical reporting is essential to ensure accurate portrayal of health and science information, which in turn can shape the health of the population.…”
Section: Introductionmentioning
confidence: 99%